128 Rapidly Proliferative Pilomatrixoma On the Eyebrow of A 7-Year-Old Boy – A Case Report. (12th October 2021) - Patel, M; Sinha, M
Abstract: Pilomatrixoma or calcifying epithelioma of Malherbe is a benign tumour originating from pluripotent precursors of hair matrix cells. We present a paediatric patient with a rapidly enlarging eyebrow mass with a differential diagnosis of sebaceous cyst, pyogenic granuloma, or malignancy. A 7-year-old boy presented in primary care with a 0.5cm non-inflammatory nodule on his medial brow present for 2-3 months. History of previous trauma was not elicited and there were no features of bleeding or ulceration. It was then lanced, following diagnosis of an infected sebaceous cyst. Within weeks, the nodule underwent rapid proliferation, enlarging to 2cm in diameter. He was urgently referred to secondary care pending further investigation for possible trauma-induced pyogenic granuloma or malignancy. Upon presentation in secondary care, we observed a protruding erythematous and ulcerated mass, indurated in texture and adherent to overlying skin. The patient was submitted to excisional biopsy with a vertical elliptical approach to minimise distortion of the brow. Small, calcified deposits were observed in the tumour substance. Histologically, basaloid basophilic cells were predominant and mixed with ghost cells and foci of giant multinucleate cells, verifying diagnosis of a pilomatrixoma. Pilomatrixoma exhibits tendency towards mimicry of lesions such as epidermoid, sebaceous, dermoid cyst, pyogenic granuloma or even keratoacanthoma with a pre-operative detection rate as low as 11%. With a bimodal age distribution, arising in the first and sixth decades of life, this case highlights a need for a high degree of suspicion in young patients with careful clinical examination in order to aid diagnosis and prompt appropriate treatment.